Radial anisotropy of the North American upper mantle based on adjoint tomography with USArray. Issue 1 (31st July 2017) - Zhu, Hejun; Komatitsch, Dimitri; Tromp, Jeroen
Summary: We use seismic data from USArray to image the upper mantle underneath the United States based on  a so-called 'adjoint tomography', an iterative full waveform inversion technique. The inversion uses data from 180 regional earthquakes recorded by 4516 seismographic stations, resulting in 586 185 frequency-dependent measurements. Three-component short-period body waves and long-period surface waves are combined to simultaneously constrain deep and shallow structures. The transversely isotropic model US22 is the result of 22 pre-conditioned conjugate-gradient iterations. Approximate Hessian maps and point-spread function tests demonstrate good illumination of the study region and limited trade-offs among different model parameters. We observe a distinct wave-speed contrast between the stable eastern US and the tectonically active western US. This boundary is well correlated with the Rocky Mountain Front. Stable cratonic regions are characterized by fast anomalies down to 250–300 km, reflecting the thickness of the North American lithosphere. Several fast anomalies are observed beneath the North American lithosphere, suggesting the possibility of lithospheric delamination. Slow wave-speed channels are imaged beneath the lithosphere, which might indicate weak asthenosphere. Beneath the mantle transition zone of the central US, an elongated north–south fast anomaly is observed, which might be the ancient subducted Farallon slab. The tectonically active western US is dominated by prominent slow anomalies with magnitudes greater than −6 per cent down to approximately 250 km. No continuous lower to upper mantle upwellings are observed beneath Yellowstone. In addition, our results confirm previously observed differences between oceans and continents in the anisotropic parameter ξ = (βh /βv ) 2 . A slow wave-speed channel with ξ > 1 is imaged beneath the eastern Pacific at depths from 100 to 200 km, reflecting horizontal shear within the asthenosphere. Underneath continental areas, regions with ξ > 1 are imaged at shallower depths around 100 km. They are characterized by fast shear wave speeds, suggesting different origins of anisotropy underneath oceans and continents. The wave speed and anisotropic signatures of the western Atlantic are similar to continental areas in comparison with the eastern Pacific. Furthermore, we observe regions with ξ < 1 beneath the tectonically active western US at depths between 300 and 400 km, which might reflect vertical flows induced by subduction of the Farallon and Juan de Fuca Plates. Comparing US22 with several previous tomographic models, we observe relatively good correlations for long-wavelength features. However, there are still large discrepancies for small-scale features.